Response in breast vs axilla after neoadjuvant treatment and implications for nonoperative management of invasive breast cancer. Issue 2 (3rd January 2021) - Schmidt, Hank; Zhaveri, Shruti; Valente, Christopher; Pisapati, Kereeti; Pickholz, Eliana; Weltz, Sarah; Nayak, Anupma; Oza, Twisha; Corben, Adriana; Weltz, Christina; Port, Elisa; Jaffer, Shabnam
Abstract: Improved imaging and neoadjuvant chemotherapy (NAT) have led to higher pathologic complete response rates (pCR) in patients with invasive breast cancer. This has questioned the necessity of surgery and axillary lymph node (ALN) dissection in these patients. Prospective clinical trials are implementing extensive core biopsies of the tumor bed of patients with clinical complete response as a means to identify and spare them breast surgery. In addition, it is anticipated that patients with pCR are most likely going to have no or minimal disease in ALN as well. To verify the feasibility of these trials, we performed a pathologic analysis of all our patients who have undergone NAT from 2009 to present. Using pathology data base, we identified 362 patients treated with neoadjuvant chemotherapy followed by surgery. Clinical and pathologic information including gross and microscopic descriptions as well as biomarker status was collected. pCR was 50% for patients with negative ALN pretreatment but only 28% for patients with positive ALN at diagnosis. Despite achieving pCR in the breast, up to 10% of patients with positive ALN and 1% with negative ALN had persistent disease. Eight percent of patients that were presumed to have no ALN disease either clinically and or by imaging were found to have metastatic carcinoma in ALN. The metastases were predominantly (80%) <5 mm, and not palpable on physical examination and or due to biopsy sampling error. pCR in breast and ALN directly correlated with tumor size, ALN disease, and Her2 positive and triple negative receptor phenotype. In breast cancer patients who are node positive at time of diagnosis with pCR in the breast after neoadjuvant chemotherapy, residual lymph node disease was very uncommon. Further study is warranted to select patients who may avoid breast and axillary surgery post neoadjuvant chemotherapy.